2021
DOI: 10.1098/rsos.202032
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for natural hybridization and novel Wolbachia strain superinfections in the Anopheles gambiae complex from Guinea

Abstract: Wolbachia , a widespread bacterium which can influence mosquito-borne pathogen transmission, has recently been detected within Anopheles ( An .) species that are malaria vectors in Sub-Saharan Africa. Although studies have reported Wolbachia strains in the An. gambiae complex, apparent low density and prevalence rates require confirmation. In this study, wild Anopheles mosquitoes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 75 publications
0
15
0
Order By: Relevance
“…This is mainly owing to the benefits of Wolbachia infections, which induce mosquitoes to produce two desirable properties for disease vector control, cytoplasmic incompatibility (CI) and pathogen inhibition ( Walker et al, 2021 ). Meanwhile, there is increasing evidence that Wolbachia infections in mosquitoes are common ( Baldini et al, 2014 ; Niang et al, 2018 ; Jeffries et al, 2021 ); 25 species of African Anopheles mosquitoes have been found to carry 16 varieties of Wolbachia infections ( Ayala et al, 2019 ). The desirable induction properties and diverse flora have prompted researchers to further increase their interest in using Wolbachia for developing biological control strategies against malaria transmission ( Figure 2 ).…”
Section: Endosymbiosis In Transmission-blocking Of Malariamentioning
confidence: 99%
“…This is mainly owing to the benefits of Wolbachia infections, which induce mosquitoes to produce two desirable properties for disease vector control, cytoplasmic incompatibility (CI) and pathogen inhibition ( Walker et al, 2021 ). Meanwhile, there is increasing evidence that Wolbachia infections in mosquitoes are common ( Baldini et al, 2014 ; Niang et al, 2018 ; Jeffries et al, 2021 ); 25 species of African Anopheles mosquitoes have been found to carry 16 varieties of Wolbachia infections ( Ayala et al, 2019 ). The desirable induction properties and diverse flora have prompted researchers to further increase their interest in using Wolbachia for developing biological control strategies against malaria transmission ( Figure 2 ).…”
Section: Endosymbiosis In Transmission-blocking Of Malariamentioning
confidence: 99%
“…stephensi . Chen et al [ 20 ] showed that An. stephensi can be stably infected by wAlbB and that there was no change in the microbiome of the mosquitoes upon Wolbachia infection.…”
Section: Introductionmentioning
confidence: 99%
“…These genes include the 16S -encoding gene, the surface protein-encoding gene (Wolbachia surface protein [ wsp ]), and the five multilocus strain typing (MLST) genes ( ftsZ , fbpA , hcpA , coxA , and gatB ) [ 10 ]. Previous studies have depended solely on Wolbachia 16S for confirming infection [ 18 , 19 ]; however, more recent research has indicated that multiple genes must be detected in order to confirm infection [ 20 ]. Very few Anopheles species have been screened for Wolbachia , with proven infection occurring only in two highly diverged species in sub-Saharan Africa [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kok-Lung Chan, a Sir Henry Dale Fellow at the University of Sussex, reviews the causes and consequences of incomplete genomic DNA replication and the role of replication stress on genomic instability [ 12 ]. Thomas Walker, a Sir Henry Dale Fellow at the London School of Hygiene and Tropical Medicine, presents research from his group on novel Wolbachia bacterial strains in populations of the mosquito Anopheles gambiae in Guinea—findings that identify further candidate strains that might be used in the future for malaria biocontrol strategies [ 13 ]. Christos Gkogkas, a Sir Henry Dale Fellow at the University of Edinburgh, contributes a timely review of recent developments in translational controls in brain development in neurons and endothelial cells, and implications for the treatment of neurodevelopmental disorders [ 14 ].…”
mentioning
confidence: 99%